PREPARASI DAN KARAKTERISASI BENTONIT TERMODIFIKASI DIMETILDIOKTADESILAMONIUM BROMIDA SERTA APLIKASINYA UNTUK ADSORPSI NAFTALENA - , Rahmat Saleh Kusuma Wardhana ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The naphthalene adsorption by dimethyldioctadecylammonium bromide (DDA) surfactant modified bentonite has been studied. The first step of this research was characterization of bentonite from Sukabumi, Boyolali, and Pacitan to determine the content of montmorilonite and cation exchange capacity (CEC). The bentonite having highest montmorilonite content and CEC value was chosen for this research. The bentonite was then treated with HCl 6 M at 95 ï°C with time variation to remove the impurities. The treated bentonite was then modified with DDA surfactant by ion exchange method at room temperature for 24 hours with variation of DDA concentration. Adsorption process of naphthalene on bentonite-DDA was carried out in batch system at room temperature with variation of naphthalene concentration and contact time. The adsorption result was calculated by subtracting the initial naphthalene concentration with the remaining unadsorbed concentration using spectrophotometer UV-Vis. The result of the research shows that bentonite from Pacitan has highest montmorilonite content which is 82.46% and CEC value which is 68.80 meq/ 100 g, so that it was chosen to be used in this research. Acid treatment of the bentonite using HCl 6 M at 95 ï°C can remove the impurities optimally without destroyed montmorilonite structure was obtained in 4 hours. Bentonite modification with DDA gave the maximum result at 0.17 M of DDA concentration or equal with one CEC value. The adsorption of naphthalene on bentonite-DDA was found as monolayer following Langmuir adsorption isotherm with adsorption capacity and adsorption energy 0.87 mg/g and 25.03 kJ/mol respectively. The adsorption kinetics of naphthalene on bentonite-DDA followed pseudo second order equation with rate constant as 0.48 g.mg-1.min-1.